Randomized Clinical Trial Comparing Reduced-Volume Oral Picosulfate and a Prepackaged Low-Residue Diet With 4-Liter PEG Solution for Bowel Preparation - Kim, Yong Sok; Hong, Chang Won; Kim, Byung Chang; Han, Kyung Su; Park, Ji Won; Seong Choi, Hyo; Joo, Jungnam; Sohn, Dae Kyung (Diseases of the colon & rectum, 2014)
BACKGROUND:Reduced-volume bowel preparation with a low-residue diet prior to colonoscopy would result in better patient compliance and sufficient bowel preparation. OBJECTIVE:To compare the clinical efficacy of reduced-volume sodium picosulfate and a prepackaged low-residue diet with that of the standard bowel preparation using 4 L of PEG solution. DESIGN:Prospective, single center, single blind, active control, randomized study (NCCCTS-12–619, KCT0000470). SETTING:Ambulatory outpatient clinic at the National Cancer Center, Republic of Korea. PATIENTS:A total of 194 subjects were randomly assigned for this study, 97 in each group. After exclusions, 94 subjects in the Picolight group and 90 in the PEG group completed the study and were analyzed. INTERVENTIONS:Sodium picosulfate with a prepackaged low-residue, one-day diet or 4-L PEG for bowel preparation. MAIN OUTCOME MEASURES:Success rate of the bowel preparation, tolerability, adverse events, cecal intubation time, polyp detection rate and adenoma detection rate. RESULTS:The bowel preparation success rate was significantly higher (91.5% vs. 81.1%, p = 0.04) and the rates of adverse events, including abdominal distension, pain, nausea, vomiting and abdominal discomfort, were significantly lower in the picosulfate group than the PEG group. Cecal intubation times and the polyp and adenoma detection rates were similar in the 2 groups. LIMITATIONS:Single center, limited population, all colonoscopies were performed in the morning. CONCLUSIONS:Bowel preparation with low-volume oral picosulfate and a prepackaged low-residue diet enhances colon cleansing and is better tolerated than the standard bowel preparation.